O jogo dos vestígios: narrador, experiência e memória a partir de Narradores de Javé - Luciana Amormino Fonseca (2009)
This dissertation investiges the relation between narrator, experience and memory nowadays, trough the analysis of the movie Narradores de Javé (Brazil, Eliane Caffé, 2003). Aiming to characterize the narratives strategies of the film, the dissertation discusses the mise-en-abîme that it presents. Each level of narrative is peculiarly constructed in terms of color, mise-en-scène and montage. Those aspects will be use as analytical operators. The narrator is understood as a textual construction that, in the case of this movie, anchor his experience in the narrated subject, like the narrators of the oral tradition. The distinct construction of their narratives emphasizes the fragmentation and the instability of memory and the difficulty of ensuring social stability through the concept of collective memory. Thus, this movie incorporates the past into itsnarrative, building narrators of oral tradition, updating the myth of origin and conforming its narrative structure through the mise-en-abîme. However, this return of the traditional ways of narrating is made by parody and play, which leads to the reflection about the relation between present and past, that pays tribute to him while pointing its failure in contemporary scene. Thus, the dissertation aims to understand certain contemporary ways to narrate, taking as reference by means of parody of elements from the past in a contemporary audiovisual narrative.